KEPERCAYAAN DIRI PESERTA EKSTRAKURIKULER TAEKWONDO DI SMA NEGERI 9 PONTIANAK - Maulidi Maulidi; Mimi Haetami; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the level of self-confidence of SMA Negeri 9 Pontianak students who take extracurricular taekwondo. Descriptive research method. Sources of data in this study amounted to 21 students. This research technique uses observation. Data analysis using percentages. The results of this study indicate that the level of self-confidence of students of SMA Negeri 9 Pontianak who take extracurricular taekwondo reaches an actual score of 566 from the ideal score of 756 which means that it reaches 74.87% of what it should be. , so it's in the "Good" category.Keywords: Self-confidence, Taekwondo.